High prevalence of blood-borne virus infections and high-risk behaviour among injecting drug users in Tallinn, Estonia. - Uusküla, Anneli; McNutt, Louise Anne; Dehovitz, Jack; Fischer, Krista; Heimer, Robert (International journal of STD & AIDS, 2007)
The HIV epidemic in Estonia is rapidly expanding, and injection drug users (IDUs) are the major risk group contributing to the expansion. A convenience sample of 159 IDUs visiting syringe-exchange programmes (SEPs) was selected to quantify the association of HIV-risk behaviours and blood-borne infections. A high prevalence of HIV, hepatitis B core antibody (HBVcore), hepatitis B surface antigen (HbsAg) and hepatitis C virus antibodies (56, 85.1, 21.3, and 96.2%, respectively) was associated with high-risk injections, unsafe sexual behaviour and alcohol abuse. These findings emphasize the importance of evidence-based secondary prevention among the HIV-infected, especially given the uncertain sustainability of antiretroviral and substance abuse treatments.
Keywords: Adolescent; Adult; Disease Transmission, Infectious; Estonia; Female; Hepacivirus; Hepatitis B; Hepatitis B virus; Hepatitis C; HIV; HIV Infections; Humans; Male; Needle-Exchange Programs; Prevalence; Questionnaires; Risk-Taking; Substance Abuse, Intravenous